2015
DOI: 10.1039/c5cs00092k
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrate nanocarriers in biomedical applications: functionalization and construction

Abstract: The specific targeting of either tumor cells or immune cells in vivo by carefully designed and appropriately surface-functionalized nanocarriers may become an effective therapeutic treatment for a variety of diseases. Carbohydrates, which are prominent biomolecules, have shown their outstanding ability in balancing the biocompatibility, stability, biodegradability, and functionality of nanocarriers. The recent applications of sugar (mono/oligosaccharides and/or polysaccharides) for the development of nanomedic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
135
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 209 publications
(137 citation statements)
references
References 172 publications
(380 reference statements)
2
135
0
Order By: Relevance
“…Encapsulation/conjugation of chemotherapeutic agents inside these vehicles protects them from degradation by physiological processes after administration, while also facilitating their transport across the cellular membrane. Additionally, their high surface functionality can be exploited by attaching specific targeting moieties (antibodies, peptides, or glycosylated moieties). These properties can lead to higher therapeutic efficacy, tumor selectivity, and reduced side effects for nanoparticle drug delivery vectors, in comparison to their molecular drug counterparts …”
Section: Introductionmentioning
confidence: 99%
“…Encapsulation/conjugation of chemotherapeutic agents inside these vehicles protects them from degradation by physiological processes after administration, while also facilitating their transport across the cellular membrane. Additionally, their high surface functionality can be exploited by attaching specific targeting moieties (antibodies, peptides, or glycosylated moieties). These properties can lead to higher therapeutic efficacy, tumor selectivity, and reduced side effects for nanoparticle drug delivery vectors, in comparison to their molecular drug counterparts …”
Section: Introductionmentioning
confidence: 99%
“…Our collaborative research center for nanoparticle-based cancer immune therapy (CRC 1066) exactly provides these desired properties [12][13][14]. Here especially physicochemical characterization techniques provide insights into the behavior of nanocarriers in complex media, like blood or intracellular fluids [15,16].…”
mentioning
confidence: 99%
“…Voit and co‐workers similarly showed that the cellular uptake of ATP is faster and greater in carcinoma cells (SKOV‐3 and HepG2) when the biomacromolecule is complexed to oligosaccharide‐shelled hyperbranched PEI and noted that such an approach could be used to increase both biocompatibility and molecular recognition. These data highlight that carbohydrates such as lactose, maltose, and glucose have great potential for balancing the stability, cytotoxicity, and biocompatibility of nanocarriers . Nevertheless, further results reveal that this behavior did not lead to higher degrees of gene expression, as shown in Figure 8 .…”
Section: Resultsmentioning
confidence: 83%